Screening of the Open Source Malaria Box Reveals an Early Lead Compound for the Treatment of Alveolar Echinococcosis. - Britta Stadelmann; Reto Rufener; Denise Aeschbacher; Markus Spiliotis; Bruno Gottstein; Andrew Hemphill (PLoS Neglected Tropical Diseases)
The metacestode (larval) stage of the tapeworm Echinococcus multilocularis causes alveolar echinococcosis (AE), a very severe and in many cases incurable disease. To date, benzimidazoles such as albendazole and mebendazole are the only approved chemotherapeutical treatment options. Benzimidazoles inhibit metacestode proliferation, but do not act parasiticidal. Thus, benzimidazoles have to be taken a lifelong, can cause adverse side effects such as hepatotoxicity, and are ineffective in some patients. We here describe a newly developed screening cascade for the evaluation of the in vitro efficacy of new compounds that includes assessment of parasiticidal activity. The Malaria Box from Medicines for Malaria Venture (MMV), comprised of 400 commercially available chemicals that show in vitro activity against Plasmodium falciparum, was repurposed. Primary screening was carried out at 10 μM by employing the previously described PGI assay, and resulted in the identification of 24 compounds that caused physical damage in metacestodes. Seven out of these 24 drugs were also active at 1 μM. Dose-response assays revealed that only 2 compounds, namely MMV665807 and MMV665794, exhibited an EC50 value below 5 μM. Assessments using human foreskin fibroblasts and Reuber rat hepatoma cells showed that the salicylanilide MMV665807 was less toxic for these two mammalian cell lines than for metacestodes. The parasiticidal activity of MMV665807 was then confirmed using isolated germinal layer cell cultures as well as metacestode vesicles by employing viability assays, and its effect on metacestodes was morphologically evaluated by electron microscopy. However, both oral and intraperitoneal application of MMV665807 to mice experimentally infected with E. multilocularis metacestodes did not result in any reduction of the parasite load.